2021
DOI: 10.1126/scirobotics.abf6354
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of robust self-organized undulatory swimming based on local hydrodynamic force sensing

Abstract: Undulatory swimming represents an ideal behavior to investigate locomotion control and the role of the underlying central and peripheral components in the spinal cord. Many vertebrate swimmers have central pattern generators and local pressure-sensitive receptors that provide information about the surrounding fluid. However, it remains difficult to study experimentally how these sensors influence motor commands in these animals. Here, using a specifically designed robot that captures the essential components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 104 publications
4
60
0
Order By: Relevance
“…Optimal sensor locations for artificial swimmers have been also investigated to improve the efficiency (Verma et al, 2019;Weber et al, 2020), especially when the number of biomimetic neuromasts is limited. The sensing of external hydrodynamic stress may improve the control robustness in single-fish self-organized undulatory swimming (Thandiackal et al, 2021), as well as the propulsive efficiency (Tytell et al, 2010). In collective swimming, the interaction of the flow field and the surface stress between neighboring fish have been established by several recent studies (Daghooghi and Borazjani, 2015;Chen et al, 2016;Peng et al, 2018, Li et al, 2019a2019b;Verma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Optimal sensor locations for artificial swimmers have been also investigated to improve the efficiency (Verma et al, 2019;Weber et al, 2020), especially when the number of biomimetic neuromasts is limited. The sensing of external hydrodynamic stress may improve the control robustness in single-fish self-organized undulatory swimming (Thandiackal et al, 2021), as well as the propulsive efficiency (Tytell et al, 2010). In collective swimming, the interaction of the flow field and the surface stress between neighboring fish have been established by several recent studies (Daghooghi and Borazjani, 2015;Chen et al, 2016;Peng et al, 2018, Li et al, 2019a2019b;Verma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because a sine-based control method has the problem of discontinuous output, artificial central pattern generators (CPGs) composed of nonlinear oscillators have become the mainstream motion control method of robots. At present, the main CPG models include Matsuoka oscillators [32,33], Hopf oscillators [22,34] and phase oscillators [35,36]. Control methods based on CPGs have been successfully applied to several fish-like robots, and switching between different behaviors has been realized.…”
Section: Introductionmentioning
confidence: 99%
“…In robotics, feedback from continuum joints is typically provided by sensing changes in length and curvature [ 14 ]. However, it has recently been demonstrated that stable swimming rhythms can be generated through sensing of hydrodynamic pressures on the body [ 17 ]. Fish possess few, if any, length sensors like muscle spindles [ 18 , 19 ], but can sense body curvature in the spinal cord and through stretching of the skin [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%